Detection of Proteases from Bacillus Species Isolated from Agricultural Soil - Bibi, Saima; Ibrahiam, Haroon; Nazir, Arzoo (Indus Journal of Bioscience Research, 2025)
Present research project was conducted to investigate the protease production by gram positive Bacillus species and to investigate their role in dehairing of animal hides. Proteases are widely employed as they have replaced the use of conventional chemical based dehairing methods as they are ecofriendly, easy to cultivate and have high productivity rate. Experimental work was conducted in September, 2022 to July, 2023. 25 agricultural soil samples were collected from different local areas of Haripur and subjected to isolation and purification of Bacillus strains using LB media. Out of 25 samples, n =19 samples showed growth on LB agar media. These samples were then screened for species confirmation, which was carried out by Culturing, Microscopy and Biochemical testing and further confirmation by MALDI-TOF. Cultural identification showed filamentous and irregular white colonies. Microscopic view showed gram positive purple rods. Biochemical tests were positive for catalase, Simmon citrate and indole test and are negative for urease, TSI and oxidase test. After MALDI-TOF out of n=19 samples, n=4 samples showed confirmation for Bacillus subtilis. These samples showed 99.9% similarity with Bacillus subtilis. The protease production of these selected strains was checked by performing protease assay using casein as a substrate. Specificity of the proteases was determined by optimum temperature (60°C) and pH (8.0). The results demonstrated that proteases exhibited stability at broad pH (8.0) and temperature (60°C). Furthermore, the potential applications of proteases in dehairing of animal hides was evaluated through enzymatic de hairing experiments using raw hides from livestock. The efficiency of proteases mediated dehairing was compared with traditional chemical and mechanical dehairing method. The findings of this study provide valuable insight into the diversity and potential of proteases produced by Bacillus species in agricultural soil and their applications in the dehairing process.